Evaluation of the diagnostic ability of the Fränkel manoeuvre to detect the contributing jaw in angle class II division 1 malocclusion - Nerija Spaičytė; Kotryna Kozlovskaja; Dalia Smailienė; Arūnas Vasiliauskas; Kristina Lopatienė; Giedrė Trakinienė (BMC, 2024)
Abstract Background A correct diagnosis of patients with an Angle Class II malocclusion is needed to guide treatment decisions toward the contributing jaw and to achieve better treatment outcomes. The aim of the study is to evaluate the diagnostic potential of the Fränkel manoeuvre (FM) for detecting the components determining sagittal discrepancy in Angle Class II division 1. Materials and methods Anonymous questionnaires containing photographs were distributed totwo groups: general practitioner (GP) dentists and orthodontists. The level of the patient's profile aesthetics before (T0) and after (T1) the manoeuvre was determined using a 100 mm visual analog scale, and the 'profile improvement' score was defined as T1 minus T0. The diagnostic ability of the FM was calculated by comparison with lateral cephalometry as a reference standard using receiver operating characteristic (ROC) curve analysis. Results A total of 102 respondents participated in the survey; 40 were orthodontists, and 62 were GP dentists. According to the post-FM images, the "profile improvement" score (T1-T0) was significantly greater in patients with mandibular retrusion than in those with maxillary protrusion (p < 0.05). The predictive power of FM, coinciding with the area under the ROC curve, was 0.62 for GPs and 0.78 for orthodontists. Conclusions The FM method is a useful and accurate tool for diagnosing skeletal Angle Class II malocclusion etiology (mandibular retrusion or maxillary protrusion), especially when used by orthodontists.